COMPARISON ANALYSIS OF COMPANY FINANCIAL PERFORMANCE IN THE TIMES BEFORE AND DURING THE COVID-19 PANDEMIC (Study on Food and Beverage Companies Listed on the IDX in 2019-2020) - Tania Ardi; Nursiam Nursiam (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to determine, measure, and analyze differences in financial performance in the period before and during the Covid-19 pandemic which was reviewed with financial ratios. This study selects food and beverage sector companies registered on the Indonesia Stock Exchange in 2019-2020 as the population. With the purposive sampling method, the number of selected samples is 30 companies. The company data were analyzed using descriptive statistical analysis and then tested the normality of the data with Kolmogorov-Smirnov. Hypothesis testing in this study used the paired sample T-test difference test. The results showed that there were no differences in the financial performance of companies in the food and beverage sector in the period before the Covid-19 pandemic and during the Covid-19 pandemic when viewed by measuring the current ratio, debt to total assets ratio, net profit margin ratio, and price-earnings ratio. . However, in measuring the total assets turn over ratio, there are differences in the company's financial performance in the period before the Covid-19 pandemic and during the Covid-19 pandemic.